The Great Revival of 1907 in Korea: Its Cause and Effect - Cho, Eunsik (Missiology, 1998)
The Great Revival of 1907 in Korea and the church growth of the 1970s have common aspects. In the early 1900s, the Korean people had experienced national misfortune and Japanese political interference. In the 1970s, the dictatorship of the military government was strongly oppressing people. Political and social unrest encouraged people to turn to God for answers.Another common thread was the church leaders' neutral attitude toward the political authority. Those two events have “dehistorical” and “denational” aspects. Missionaries of the 1900s and pastors of the 1970s changed the direction of mission or ministry from national concerns to spiritual dimensions, and from being against injustice to obeying authority. As a result, the Korean church grew in numbers, but the Korean church minimized its social concerns and forgot its prophetic role in society.One of the important lessons is that although people had a certain intention or plan, the Holy Spirit worked in different ways through those events.